PERUBAHAN PARADIGMA PERAN POLITIK PEMUDA ISLAM INDONESIA DARI MASA KE MASA - IFA AVIANTY (Jurnal Dialog, 2016)
Young generations might be deemed as backbone of a state. They hold the ideology state to be implemented in actions. It was recorded in the history of Indonesia that young generations, particularly Islamic young generation have contributed to establish the foundations of state and pave the door to independence. They also mobilized the reformation to Soeharto’s new order regime that people could benefit the results of it. Recently, the spirit of Islamic young generations to contribute in politics apparently decreases significantly. They are in favor to be passive groups and even ignore to the dynamics of Indonesia politics. So, what are the causes of this? Is it because of materialism lifestyle? This article explains some causes of this inclination while comparing to the role of last young generation in some era of Indonesia history.